Criminological Aspects of Children as Perpetrators in the Crime of Trafficking in Persons (TPPO) - Al Farizi, Fathan; Sairi, Sairi; Fatikhaturrizqiyyah, Tika; Waluyadi, Waluyadi; Hendra, Raden (Jurnal Legisci, 2024)
The goal of this study is to inform the public about the findings to support the adoption of laws that penalize those who engage in human trafficking. The study's focus is on legal criminology, namely how to apply punishments against those who commit crimes related to human trafficking and countermeasures against juvenile offenders. This study is about legal normative research. The data gathering technique was done through literature studies and interviews for primary data, document studies for secondary data, and interviews for secondary data. The primary data was used as supporting data. A qualitative analysis and descriptive presentation of the data are made. According to the study, there are several reasons why kids commit crimes related to human trafficking.